2015
DOI: 10.1021/acs.chemmater.5b00389
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Initial Stages of Reversible Mg Deposition and Stripping in Inorganic Nonaqueous Electrolytes

Abstract: Multi-valent (MV) battery architectures based on pairing a Mg metal anode with a high-voltage (∼ 3 V) intercalation cathode offer a realistic design pathway toward significantly surpassing the energy storage performance of traditional Li-ion based batteries, but there are currently only few electrolyte systems that support reversible Mg deposition. Using both static first-principles calculations and ab initio molecular dynamics, we perform a comprehensive adsorption study of several salt and solvent species at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 42 publications
3
111
0
3
Order By: Relevance
“…A magnesium deposition-dissolution mechanism has been proposed, whereby some cationic magnesium halide complexes have mediated interface charge-transfer probes, preventing the formation of a passivation layer on the deposited magnesium. 13,18 The change in the overpotential by the content of EtMgBr appears to correspond with such previous reports. The existence of EtMgBr reduces the overpotential, even for content as low as 17%.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A magnesium deposition-dissolution mechanism has been proposed, whereby some cationic magnesium halide complexes have mediated interface charge-transfer probes, preventing the formation of a passivation layer on the deposited magnesium. 13,18 The change in the overpotential by the content of EtMgBr appears to correspond with such previous reports. The existence of EtMgBr reduces the overpotential, even for content as low as 17%.…”
Section: Resultssupporting
confidence: 89%
“…They aid the charge transfer of magnesium by changing ligands. 11,[13][14][15][16][17][18] Despite these advantages, the high reactivity of alkylmagnesium halides and anodic instability of ether solvent (typically tetrahydrofuran THF) prevents this ideal system from use in practical batteries.…”
Section: Introductionmentioning
confidence: 99%
“…al. 16 Recently, Aurbach et al revealed that the activity and composition of the MACC electrolyte (the magnesium aluminum chloride complex electrolyte, similar composition with APC electrolyte) varies with cycling. 57 Furthermore, the work done by Gewirth et al showed that the coordinated THF molecules (which with RMg + species formed at the surface of electrode) are more easily oxidized to GBL (γ-butyrolactone) due to the presence of Lewis acidity of RMg + , compared with the uncoordinated THF molecules.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Lithiumionen-Batterien sind die fortgeschrittensten kommerziell erhältlichen Energiespeicher.D emgegenüber hat der Wunsch nach einer wesentlich grçßeren Energiedichte für ein starkes Interesse an mçglichen Nachfolgetechniken wie Lithium-Luft-und Lithium-Schwefel-Batterien, multivalenten Batterien und Feststoffbatterien gesorgt. [14][15][16][17][18][19][20] Die Verwendung von Magnesium-anstelle von Lithiummetall als Anodenmaterial hat viele Vorteile,wie die Verdoppelung der volumenspezifischen Kapazität, nichtdendritisches Verhalten und geringere Kosten. Ein großer Vorteil der neuen Te chniken besteht im Ersatz der lithiierten Graphitanode,d ie sich auf einem Stromabnehmer aus Kupfer als Träger befindet, durch eine Metallanode.L ithiummetall gilt als aussichtsreicher Kandidat fürd as Anodenmaterial von Lithium-Luft-und Lithium-Schwefel-Batterien, mit dem sich Eigengewicht, das keinen Beitrag zur Kapazitätd er Anode leistet, vermeiden lässt.…”
Section: Introductionunclassified